Hadith #6319 - Sahih al-Bukhari - Hammad from 'Amr from Jabir (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Some people will come out of the Fire through intercession looking like The Thaarir.” I asked `Amr, “What is the Thaarir?” He said, Ad Dagh`Abis, and at that time he was toothless. Hammad added: I said to `Amr bin Dinar, “O Abu Muhammad! Did you hear Jabir bin `Abdullah saying, ‘I heard the Prophet (ﷺ) saying: ‘Some people will come out of the Fire through intercession?” He said, “Yes. “
Grade: Sahih